2010
DOI: 10.1007/s11858-010-0263-8
|View full text |Cite
|
Sign up to set email alerts
|

A case study: assessment of preservice secondary mathematics teachers’ metacognitive behaviour in the problem-solving process

Abstract: The purpose of the present study was to investigate preservice secondary mathematics teachers' metacognitive behaviour in the mathematical problemsolving process. The case study methodology was employed with six preservice mathematics teachers, enrolled at one university in Ankara, Turkey. We collected data by using the think aloud method, which lasted for two sessions. It was found that there was no relationship between academic achievement and frequencies of metacognitive behaviour. However, the types of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
4
0
4
Order By: Relevance
“…Demircioğlu, Argün and Bulut [32] emphasized the same result. The researchers were not encountered with any pattern demonstrated by the pre-service teachers in terms of metacognitive in their academic success, but reached the result that different types of the problems affect the number of metacognitive behaviours.…”
Section: Conclusion and Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Demircioğlu, Argün and Bulut [32] emphasized the same result. The researchers were not encountered with any pattern demonstrated by the pre-service teachers in terms of metacognitive in their academic success, but reached the result that different types of the problems affect the number of metacognitive behaviours.…”
Section: Conclusion and Discussionmentioning
confidence: 52%
“…The results of the analysis indicated that the metacognitive behaviours of pre-service teachers in this five-stage model were not linear or single-directional. A study was carried out by Demircioğlu, Argün and Bulut [32] aiming to evaluate the metacognitive behaviours of pre-service secondary school mathematics teachers in problem solving process. From the results of the study, it was reached that there was no relation between the academic success of pre-service teachers and the frequency of demonstrated metacognitive behaviour, yet, it was realised that the type of the problem affected this frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Hendriana & Soemarmo (2014) mengatakan bahwa kemampuan dasar matematik yang harus tertanam pada diri siswa, khususnya siswa pada pendidikan sekolah menengah adalah Kemampuan pemecahan masalah matematika. Selain itu, Demercioglu, Argun, & Bulut (2010), juga menjelaskan bahwa kemampuan pemecahan masalah matematika merupakan jantung dan tujuan umum dalam pembelajaran matematika. Pemecahan masalah juga dijelaskan oleh Polya (Hobri, 2009;Tohir, Susanto, Hobri, Suharto, & Dafik, 2018) sebagai suatu upaya dalam mencari jalan keluar atau solusi dari kesulitan-kesulitan yang sedang dihadapi untuk mencapai suatu tujuan yang tidak dapat segera bisa dicapai.…”
Section: Pendahuluanunclassified
“…Understanding pre-service teachers' problem solving processes may help to improve their students' abilities and their approaches to the solution of problems (Demircioğlu, Argün, & Bulut, 2010). In addition, this study presents a practical application for problem solving activities by using dynamic geometry environments in classrooms.…”
Section: Purpose Of the Studymentioning
confidence: 99%